Sports injuries in handball players of the national team in Japan - Katou, K.; Tomida, Y.; Gamo, S.; Kono, T.; Uchida, A. (5th IOC World Congress on Sport Sciences with the Annual Conference of Science and Medicine in Sport 1999, 1999)
Handball is a ball game played at high speeds with consistent physical contact, as the players are required to make full use of their bodies in both offense and defense. Both instantaneous power and endurance are needed, and it is important to have physical power and to be able to overcome sports injuries. The purpose of this study was to investigate the effect of physical strength on the occurrence of acute and overuse chronic injuries in male players of the National Handball Team of Japan.